Imagens sociais e infância: concepções e estigmas - Scott, Juliano Beck (2016)
This study is an extract from a cross-cultural research between Brazil and Portugal, which had the intention to know the social images of institutionalized and non-institutionalized children and youths as well as their families. Thereby, data collected in Brazil related to children in average and low socioeconomic status alongside with data on children in institutional care were used, configuring a quantitative and qualitative study. Study participants were 83 adults living in three municipalities of Rio Grande do Sul state aged between 16 and 62 years-old (M = 31.99, SD = 11.46) who indicated 648 characteristics to describe children of different contexts (institutionalized and from average and low socioeconomic status). An open questionnaire was used and data analysis took place in three stages: the first stage consisted of content analysis, the second was a judges consensus analysis and the third was a frequencies analysis. These steps led to the final identification of 404 attributes associated with the aim of this study. The results showed a predominance of negative images related to children belonging to low socioeconomic status and institutionalized children, opposed to children belonging to an average socioeconomic status in which more positive images predominated. The Z test found significant differences in all categories of analysis to institutionalized children, and the negative aspects were more frequent than the positive ones. Moreover, institutionalized children were portrayed negatively when compared to children in average socioeconomic status in the categories Safety and Protection, Interpersonal Attitudes and Affection, and in the categories Safety and Protection and Affection when compared to children of low socioeconomic status, showing a process of stigmatization. This demonstrates that there are negative beliefs about poor and institutionalized children which interfere with their social integration due to discrimination, exclusion and stereotyping. It is up to society to promote changes that transform these preconceived social images about these children, enforcing what is proposed by current regulation that defend their rights and recognize their status as citizens.